2015
DOI: 10.1002/ccd.26163
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in acute and 30‐day outcomes after orbital atherectomy treatment of de novo, severely calcified coronary lesions

Abstract: Despite females being older, having smaller arteries, and more renal dysfunction, preparation of severely calcified coronary lesions with orbital atherectomy to facilitate stent deployment results in similar rates of in-hospital and 30-day MACE, irrespective of gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Numerous ORBIT II sub-analyses have been published [53][54][55][56]66,67]. For example, a gender sub-analysis indicated no difference in primary safety and efficacy endpoints; however, females had an increased risk for severe dissection [53]. This finding was not consistent with a recent large coronary OAS registry which reported that the rate of dissection did not differ by gender [53,62].…”
Section: Orbit II Trial (Pivotal)mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous ORBIT II sub-analyses have been published [53][54][55][56]66,67]. For example, a gender sub-analysis indicated no difference in primary safety and efficacy endpoints; however, females had an increased risk for severe dissection [53]. This finding was not consistent with a recent large coronary OAS registry which reported that the rate of dissection did not differ by gender [53,62].…”
Section: Orbit II Trial (Pivotal)mentioning
confidence: 99%
“…The low rate of TLR/TVR in the ORBIT II trial continued out to 3 years (Table 4) [51]. Numerous ORBIT II sub-analyses have been published [53][54][55][56]66,67]. For example, a gender sub-analysis indicated no difference in primary safety and efficacy endpoints; however, females had an increased risk for severe dissection [53].…”
Section: Orbit II Trial (Pivotal)mentioning
confidence: 99%
“…11 Similarly, in the prospective, multicenter ORBIT II study, women undergoing orbital atherectomy had a higher risk of coronary dissection than men (OR 4.2; 95% CI 1.5-11.4, P ¼ .005). 12 Mechanisms of vascular injury in women may be due to direct mechanical injury related to smaller coronary arteries and higher burr:artery and balloon:artery ratios, increasing the risk of procedural complications. 32,33 Inherent vascular fragility has been reported in postmenopausal women, who represent most women undergoing PCI of calcied lesions.…”
Section: Discussionmentioning
confidence: 99%
“…11 Similar results have been reported with orbital atherctomy. 12 Acute procedural complications in women may limit the use of atherectomy to optimize DES expansion (one of the strongest predictors of subsequent stent thrombosis and restenosis 13,14 ) and likely contribute to the poor outcomes reported in the longer term.…”
mentioning
confidence: 99%
“…In this month's edition of the journal, Kim et al present a gender‐based analysis from the ORBIT II study . In light of the under‐representation of women in PCI trials and the plea from stakeholders for sex‐based analyses, particularly in device trials, this comparison is welcomed.…”
mentioning
confidence: 99%